Proceedings of the Symposium on Eye Tracking Research and Applications 2012
DOI: 10.1145/2168556.2168624
|View full text |Cite
|
Sign up to set email alerts
|

Towards location-aware mobile eye tracking

Abstract: This paper considers the impact of location as context in mobile eye tracking studies that extend to large-scale spaces, such as pedestrian wayfinding studies. It shows how adding a subject's location to her gaze data enhances the possibilities for data visualization and analysis. Results from an explorative pilot study on mobile map usage with a pedestrian audio guide demonstrate that the combined recording and analysis of gaze and position can help to tackle research questions on human spatial problem solvin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
24
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
5
3
1

Relationship

4
5

Authors

Journals

citations
Cited by 39 publications
(25 citation statements)
references
References 16 publications
1
24
0
Order By: Relevance
“…We have previously reported on an exploratory pilot wayfinding study with mobile eye tracking in Zurich (Kiefer et al. 2012a, b). First indications were found that gaze patterns on the map and in the environment differ between successful and unsuccessful participants in a wayfinding task.…”
Section: Related Work: Eye Tracking In Gisciencementioning
confidence: 99%
“…We have previously reported on an exploratory pilot wayfinding study with mobile eye tracking in Zurich (Kiefer et al. 2012a, b). First indications were found that gaze patterns on the map and in the environment differ between successful and unsuccessful participants in a wayfinding task.…”
Section: Related Work: Eye Tracking In Gisciencementioning
confidence: 99%
“…Therefore, researchers are now executing a growing number of experiments in real-world environments. Multiple eye tracking experiments exist that analyze pedestrians' [Brügger et al 2018;Davoudian and Raynham 2012;Fotios et al 2015a,b;Kiefer et al 2014Kiefer et al , 2012Wenczel et al 2017] or cyclists' behavior [Mantuano et al 2016;Schmidt and von Stülp-nagel 2018;Vansteenkiste et al 2014]. In contrast to existing works, we are presenting a visual analytics-based approach to explore patterns, extract common eye movement strategies, and enable a combined analysis of the multi-modal data.…”
Section: Related Workmentioning
confidence: 99%
“…Whereas researchers have analyzed the visual perception of car drivers in many eye tracking experiments [Kapitaniak et al 2015], there are only few experiments performed with pedestrians and cyclists. In recent years, researchers have published a growing number of eye tracking experiments analyzing pedestrians and cyclists (e. g., [Davoudian and Raynham 2012;Kiefer et al 2012;Mantuano et al 2016;Vansteenkiste et al 2014;Wenczel et al 2017]). In this paper, we apply a visual analyticsbased method to analyze gaze behavior of pedestrians and cyclists in a real-world eye tracking experiment.…”
Section: Introductionmentioning
confidence: 99%
“…From a hardware perspective, eye tracking is becoming increasingly mobile: head-mounted mobile eye trackers are used in research already today [14], and it is only a small step for eye tracking to be integrated into mobile consumer products, such as smartphones 2 or augmented reality glasses 3 .…”
Section: Gaze-based Assistancementioning
confidence: 99%